2020
DOI: 10.1093/pm/pnaa176
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining High-Quality Multidisciplinary Pain Medicine Fellowship Programs: Part II: Innovations in Clinical Care Workflow, Clinical Supervision, Job Satisfaction, and Postgraduation Mentorship for Pain Fellows During the COVID-19 Pandemic

Abstract: Background Pain fellowship programs are facing unique challenges during the COVID-19 pandemic. Restrictions by state governments and the Centers for Disease Control and Prevention have resulted in a rapidly changing and evolving learning environment for today’s fellows. Innovative solutions must be sought to maintain proper education and ensure the well-being of our trainees. Methods We assembled a panel of pain program direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…6 US directors of pain programmes have developed detailed guidance on adapting training. 7,8 Many countries have redeployed non-anaesthesia trainees to ICU, an unsettling and challenging time for those affected. 9 In Dublin, anaesthesia trainees supported redeployed peers from surgery and psychiatry introducing them to ICU in a safe and controlled manner.…”
Section: Teachingmentioning
confidence: 99%
“…6 US directors of pain programmes have developed detailed guidance on adapting training. 7,8 Many countries have redeployed non-anaesthesia trainees to ICU, an unsettling and challenging time for those affected. 9 In Dublin, anaesthesia trainees supported redeployed peers from surgery and psychiatry introducing them to ICU in a safe and controlled manner.…”
Section: Teachingmentioning
confidence: 99%
“…Telemedicine is incorporated as a training tool for the new generation of pain practitioners. The possibility that telehealth may not dissolve has pivoted training programs to include telemedicine training as part of their curriculum [ 64 ]. Millennial trainees may absorb this information and direct the improvement of the telemedicine platform.…”
Section: Insurance-related Factorsmentioning
confidence: 99%
“…It has been suggested that managing expectations of both patients and health care providers is valuable in maintaining a mutual appreciation for changes in organizational and care structures while managing the COVID-19 crisis [ 8 ]. One participant stated, “my plans were dashed when this little thing call ‘COVID-19’ decided to show up and flip the whole world upside down.…”
Section: Resultsmentioning
confidence: 99%